2019
DOI: 10.3390/jcm8091379
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Fibroblast-Dependent Androgen Receptor Activation in Prostate Cancer Cells is Involved in the Mechanism of Acquired Resistance to Castration

Abstract: Loss of androgen receptor (AR) dependency in prostate cancer (PCa) cells is associated with progression to castration-resistant prostate cancer (CRPC). The tumor stroma is enriched in fibroblasts that secrete AR-activating factors. To investigate the roles of fibroblasts in AR activation under androgen deprivation, we used three sublines of androgen-sensitive LNCaP cells (E9 and F10 cells: low androgen sensitivity; and AIDL cells: androgen insensitivity) and original fibroblasts derived from patients with PCa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…LNCaP cells were cocultured with each of four patient‐derived fibroblast lines (PrSC, pcPrF‐M5, pcPrF‐M28, and pcPrF‐M31) in six‐well plates using cell culture inserts (BD Falcon) as described previously 14 . LNCaP cells (16 × 10 4 /well) were seeded into six‐well plates in phenol red (+) RPMI‐1640 supplemented with 10% FBS, whereas patient‐derived fibroblasts (PrSC, pcPrF‐M5, pcPrF‐M28, and pcPrF‐M31; 2 × 10 4 /well) were seeded into cell culture inserts containing SCBM medium for 3 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LNCaP cells were cocultured with each of four patient‐derived fibroblast lines (PrSC, pcPrF‐M5, pcPrF‐M28, and pcPrF‐M31) in six‐well plates using cell culture inserts (BD Falcon) as described previously 14 . LNCaP cells (16 × 10 4 /well) were seeded into six‐well plates in phenol red (+) RPMI‐1640 supplemented with 10% FBS, whereas patient‐derived fibroblasts (PrSC, pcPrF‐M5, pcPrF‐M28, and pcPrF‐M31; 2 × 10 4 /well) were seeded into cell culture inserts containing SCBM medium for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…Within a focal lesion, CAFs heterotypically communicate with PCa cells not only by direct cell–cell contact via cell adhesion molecules but also by indirect cell–cell communication via soluble factors 4 . In our experience, however, in vivo or in vitro cocultures of PCa cells and CAFs are not able to recapitulate the histopathology of PCa tissues; for example, PCa cells invade the thick stromal layer, which resembles human prostate stromal structures 8,9,14 To visualize the heterotypic interactions between PCa cells and CAFs, we focused on the contractile activity of CAFs and their clumping on a viscous substrate 15,16 Finally, we developed a novel three‐dimensional (3D) coculture protocol to simulate PCa cell invasion in the reactive stroma.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have also shown that fibroblasts from patients with advanced PCa promote proliferation in PCa cells. 12,13 However, all fibroblasts from patients with advanced PCa do not promote proliferation in PCa cells. To determine the biochemical characteristics of fibroblasts, it is necessary to understand not only the effects of growth factors and cytokines on PCa cell behavior but also the effects of other fibroblast-derived soluble factors on cancer cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…14 Fibroblast-derived growth factors and cytokines promote the proliferation of PCa cells independent of androgen sensitivity and AR dependency. 13 In addition, ARactivating factor-secreted PCa patient-derived fibroblasts induce a cord-like infiltrating growth pattern in PCa cells. 15 These fibroblasts affect the expression levels of various genes, such as CDH2, in androgen-sensitive, ARdependent PCa cells.…”
Section: Introductionmentioning
confidence: 99%
“…AR expression in PC CAFs provides a good prognosis, but a loss of AR [ 454 ] and of fibroblast-dependent androgen activation may be responsible for PC progression [ 455 ]. Spontaneously immortalized stromal fibroblasts [ 456 ] promote the growth and progression of prostate tumors in mice, and stroma can induce permanent gene expression and behavior changes in epithelial cells [ 200 ].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%